Studi Produksi dan Karakterisasi Komposisi Kimia Beberapa Kategori Asap Cair dari Tempurung Lontar (Borassus flabellifer L.) - Sarifudin, Kasimir; Naibaus, Richard Veqiyanus; Parera, Lolita A.M. (Pendidikan MIPA Universitas Nusa Cendana, 2024)
This study aims to investigate the production and characterization of the chemical composition of various quality classifications of liquid smoke that is derived from lontar Shells. Liquid smoke is generated from dried lontar shell raw material that takes on pyrolysis at approximately 400 ℃. A vertical column-model pyrolyzer equipped with a 6-meter-long spiral-shaped condenser supports the productivity of the pyrolysis process. After being collected, the liquid smoke is allowed to settle for a duration of seven days. The process involves distillation at 130℃, followed by purification through a zeolite column and activated charcoal derived from lontar shells, resulting in grades 3, 2, and 1. The characterization of the chemical composition of each liquid smoke grade was conducted using GC-MS, in addition to the determination of acidity via acid-base titration. The findings indicate that the average yield of liquid smoke derived from dried lontar shells is 44.35% of the weight of the initial raw material. The composition of grade 3 liquid smoke includes p-cresol at 18.28%, phenol (2-methyl) at 14.79%, and phenol (2-methoxy) at 10.09%. It also has an acid content of 5.97% and contains a total of 50 compounds. The acid content of grade 2 liquid smoke is 8.70%, with p-Cresol being the most dominant component at 20.70%. Other significant constituents include phenol, 2-methoxy at 14.51%, and phenol, 3-methyl at 11.69%. The acid content of grade 1 liquid smoke is measured at 9.23%. The primary components include p-Cresol at 20.29%, followed by phenol, 3-methyl at 16.36%, and phenol, 2-methoxy at 16.18%.